APLIKASI SISTEM INFORMASI PERSONALIA CV. MADYA MANDIRI TEKNIK BERBASIS WEB DENGAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Alfiansyah; Widyat Nurcahyo; NM Faizah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2022)
Various technologies can be felt related to progress and innovation in information processing. The emergence of problems is the background for innovations in the field of technology. Information systems are a solution to help with daily work. Utilization of information systems can make work more detailed and as a place to store and process data. The application of Rapid Application Development is able to complete the creation of a data information system in a short time. The developed information system is used to assist the company's business processes in assisting data processing. In the current research, the authors develop a data information system whose purpose is to manage data in the company CV Madya Mandiri Teknik. The author created a web-based personnel information system application to help companies access data, which previously still used Microsoft Excel to record data, this was very ineffective for staffing staff in terms of efficiency in terms of costs. By designing a web-based data collection application that will make it easier for staffing staff to find out the number and status, it is hoped that it can help staffing staff to get valid data and with a variety of interesting features making it easier for administrative staff to complete their tasks effectively.